Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1099/vir.0.81023-0
|View full text |Cite
|
Sign up to set email alerts
|

T1764G1766 core promoter double mutants are restricted to Hepatitis B virus strains with an A1757 and are common in genotype D

Abstract: To investigate the role of pre-core and basal core promoter (BCP) mutants in hepatitis B e antigen (HBeAg)-negative chronic hepatitis B (e-CHB) in Iran, Hepatitis B virus strains from 30 patients and 42 anti-HBe-positive asymptomatic carriers (ASCs) were characterized. G 1896 A pre-core stop mutants, detected in 77 % of e-CHB patients and 85 % of ASCs, showed no association with virus load or aminotransferase levels. Twenty per cent of e-CHB patients and 31 % of ASCs harboured T 1762 A 1764 mutants. When this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
29
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 43 publications
13
29
0
Order By: Relevance
“…All patients were enrolled in the study after giving informed consent. Clinical characteristics of patients were previously described 17, and all patients were shown to be infected with HBV genotype D 17.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients were enrolled in the study after giving informed consent. Clinical characteristics of patients were previously described 17, and all patients were shown to be infected with HBV genotype D 17.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we characterized the BCP and preC regions of HBV isolates of Iranian patients with e-CHB, and asymptomatic carriers (ASCs) 17. The present study investigates the prevalence of mutations in different HBc immune epitopes of HBV strains in the previously studied Iranian patients and its association to serum levels of HBV DNA, aminotransferase levels, and also BCP and preC mutational patterns.…”
Section: Objectivesmentioning
confidence: 96%
See 1 more Smart Citation
“…Even in the same genotype, the significance of the clinical difference varied as a function of the subgenotype [Duong et al, 2004]. These findings indicate the clinical significance of subgenotypes and geographical variation in the prevalence of BCP and Pre-C mutations [Funk et al, 2002;Sendi et al, 2005]. HBV infection in the Solomon Islands is still highly endemic, and the genotype is ethnicity-specific.…”
mentioning
confidence: 89%
“…However, it remains unclear whether these mutations in HBV/D could affect HBeAg secretion, because nt 1846 is located outside the encapsidation signal [Kramvis and Kew, 1998]. A recent study in an Iranian population [Sendi et al, 2005] mutations, were found against the strains in Iran. Moreover, no relation to the viral load was shown in these mutations.…”
mentioning
confidence: 99%